Hubungan Antara Indeks Massa Tubuh Dengan Kejadian Hipertensi Pada Remaja Di Smk Muhammadiyah Singosari Kabupaten Malang - Dewi, Erlina Puspita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: to identify the relationship between Body Mass Index and hypertension in adolescents at SMK Muhammadiyah Singosari Malang Regency. Methods: This article is a quantitative study using a descriptive analytical design with a cross-sectional study approach. The sample in this study was 74 students at SMK Muhammadiyah Singosari Malang obtained from the simple random sampling technique. Data collection was carried out by analytical survey and observation with an instrument in the form of an observation sheet. The statistical test used in this study was the Chi Square Test which was used to determine the relationship between body mass index and the incidence of hypertension in adolescents at SMK Muhammadiyah Singosari Malang Regency. Results: the number of adolescents detected to have prehypertension was 30 students or 40.5% and 11 adolescents had hypertension with blood pressure between 130/80 - 160/100 mmHg. Adolescents who were detected to have high blood pressure had an overweight and obesity BMI of 1, namely 10 adolescents who had an overweight BMI with prehypertension then 5 pre-hypertension adolescents with an obesity BMI of 1. In addition, 3 other adolescents had an overweight BMI and were detected to have grade 1 hypertension and 4 adolescents had an obesity BMI with grade 1 hypertension blood pressure. The results of the chi square test analysis were ρ = (0.000) < (0.005) so that the decision of the Ha hypothesis was accepted, namely that there was a relationship between body mass index and the incidence of hypertension in adolescents at SMK Muhammadiyah Singosari, Malang Regency. Conclusion: Almost half of the adolescent students experience prehypertension and this is related to their body mass, so it can be concluded that there is a relationship between body mass index and hypertension in adolescents at SMK Muhammadiyah Singosari, Malang Regency.